Integrasi-Interkoneksi Pendidikan pada Sekolah Berbasis Pesantren di SMK Diponegoro Yogyakarta - Choirul Muna (Journal of Southeast Asian Islam and Society, 2023)
The rapid development of education is a sign that educational institutions must be quick and responsive in responding to this reality. In vocational schools, schools must be required to always produce graduates who are always needed by the industrial world. However, an education system that focuses solely on the demands of work backfires. One of the impacts that arise if only focusing on the demands of the industry will cause decadence, for example in aspects of personality, religious and cultural insights and partial emotional intelligence. Therefore, it is necessary to intervene in one of them in the form of integration-interconnection of Education. This study aims to examine the implementation of integration-interconnection of education in Islamic boarding school based at Diponegoro Vocational High School, Yogyakarta. This research is a field research with descriptive-qualitative type. The approach used in this study is using random cluster technique through observation, interview and literature review. The results showed that there are efforts made by schools in realizing the integration-interconnection of Education. The effort is through three elements, namely Religion, Science and education. However, there are still some obstacles in its implementation, such as learning approach factors, curriculum change factors and factors of competence of teachers. However, the result of the combination of these three elements is expected to contribute in the form of superior values, skilled, religious, independent and akhlaqul karimah.